Energy expenditure and movement activity analysis of sepaktakraw players in the Thailand league - Kacha Udomtaku; Kurusart Konharn (Elsevier, 2020)
Background/Objective: The analysis of energy expenditure (EE) and movement activity in specific positions among sepaktakraw players during competition is important for planning training and appropriate nutrition programs. The study aimed to compare the EE and movement activity of different positions among sepaktakraw players during competition. Methods: Forty-two sepaktakraw players in the Thailand League, assigned to 1 of 3 positions - servers (n = 14), feeders (n = 14), and strikers (n = 14) - aged 20-40 years, were asked to wear a GT9X ActiGraph on the upper Achilles tendon of their dominant leg during a simulated competitive match. Results: Servers and strikers showed a higher activity kcal and MET than feeders (p < 0.01). Servers (4914.32 ± 509.041 CPM) and strikers (4655.38 ± 557.64 CPM) performed in vertical axis movement more than feeders (3428.11 ± 453.86CPM) (p < 0.01). Conclusions: The results of the study will aid in designing specific training programs based on playing positions, so as to provide the athletes with the appropriate and consistent energy intake required and the direction of movement with specific positions.